¿Dedicó Isidoro de Sevilla las "Etymologiae" al rey Sisebuto? / Did Isidore of Seville dedicate the Etymologiae to the King Sisebuto? - Valeriano Yarza Urquiola (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2018)
Despite hesitation, the prevailing opinion among scholars today is that Isidore dedicated his masterpiece, Etymologiae, to the visigoth king Sisebuto (612-621). We are not entirely sure about such estimation and in this article we are aiming at providing information and arguments to rebut or, at least, call it into question.